2006
DOI: 10.1097/01.fjc.0000191564.52242.00
|View full text |Cite
|
Sign up to set email alerts
|

Block of hERG Channels by Berberine

Abstract: Berberine prolongs the duration of cardiac action potentials without affecting resting membrane potential or action potential amplitude. Controversy exists regarding whether berberine exerts this action by preferential block of different components of the delayed rectifying potassium current, I(Kr) and I(Ks). Here we have studied the effects of berberine on hERG (I(Kr)) and KCNQ1/KCNE1 (I(Ks)) channels expressed in HEK-293 cells and Xenopus oocytes. In HEK-293 cells, the IC50 for berberine was 3.1 +/- 0.5 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…At concentrations similar to the IC 50 of ≈3 µM for CGN viability, BBR inhibits delayed rectifier currents and HERG channels [15], [25], [68]. At higher concentrations, BBR also inhibits a variety of potassium currents, including inward and outward rectifier, voltage sensitive, and K + channel currents [25], [67][69].…”
Section: Discussionmentioning
confidence: 92%
“…At concentrations similar to the IC 50 of ≈3 µM for CGN viability, BBR inhibits delayed rectifier currents and HERG channels [15], [25], [68]. At higher concentrations, BBR also inhibits a variety of potassium currents, including inward and outward rectifier, voltage sensitive, and K + channel currents [25], [67][69].…”
Section: Discussionmentioning
confidence: 92%
“…BBR, at the dosage of 100 mg/kg/day, plays positive inotropic, antiarrhythmic, and vasodilator properties related to the cardiovascular system [ 188 , 189 ]. The antiarrhythmic effects are due, at least in part, to preferential blockade of the components of the delayed rectifying potassium current, I(Kr), and I(Ks) and to increased effective refractory period of Purkinje fibers [ 190 , 191 ].…”
Section: Berberinementioning
confidence: 99%
“…To clarify whether hERG channel deficiency caused by BBR incubation was also on account of Phe656 and Tyr652 binding similar to acute application of BBR. 8 We studied the effects of BBR on mutant channels by transfecting HEK293 cells with WT-hERG, Y652A-hERG, or F656V-hERG. Figure 2A shows Western blot analysis and statistics.…”
Section: Resultsmentioning
confidence: 99%
“…Previous researches showed that BBR acutely blocks hERG channel in Xenopus oocytes by interacting with the two aromatic amino acid residues (tyrosine [Tyr652] and phenylalanine [Phe656], which are thought as the universal binding sites for various hERG channel blockers) located in S6 transmembrane helix. 8 Drug binding to special residues may induce conformational changes of the hERG channel. 9 In addition, we recently reported that BBR reduces hERG plasma membrane expression, through disrupting trafficking after long-term exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation